1988
DOI: 10.1099/0022-1317-69-8-2033
|View full text |Cite
|
Sign up to set email alerts
|

Gene Sequence and Mapping Data from Marek's Disease Virus and Herpesvirus of Turkeys: Implications for Herpesvirus Classification

Abstract: SUMMARYPurified DNAs from Marek's disease virus (MDV) and the herpesvirus of turkeys (HVT) were randomly sheared and cloned into the M 13 bacteriophage. Two-hundred and ten MDV and 130 HVT clones were sequenced to give representative samples of the genome sequences. The predicted amino acid sequences from these gammaherpesviruses were compared to known sequences from other herpesviruses using computer analysis. Thirty-five MDV and 24 HVT genes were identified by comparison with varicella-zoster virus (VZV), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
88
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 41 publications
3
88
0
Order By: Relevance
“…Recently, Buckmaster et al (1988) identified 35 MDV genes by comparing the translated sequence of random fragments of MDV DNA with the amino acid sequences of known herpesvirus proteins. Most of the genes identified mapped in the UL region and were coUinear with genes of the alphaherpesviruses herpes simplex virus (HSV) and varicella-zoster virus (VZV).…”
mentioning
confidence: 99%
“…Recently, Buckmaster et al (1988) identified 35 MDV genes by comparing the translated sequence of random fragments of MDV DNA with the amino acid sequences of known herpesvirus proteins. Most of the genes identified mapped in the UL region and were coUinear with genes of the alphaherpesviruses herpes simplex virus (HSV) and varicella-zoster virus (VZV).…”
mentioning
confidence: 99%
“…Such an approach has been used previously to determine rapidly the overall conservation of gene order and genetic relatedness of the gammaherpesviruses EBV and HVS (Gompels et al, 1988), and the close genetic relationship of MDV with the alphaherpesviruses VZV and HSV (Buckmaster et al, 1988). We have identified nine genes in MHV-68 which are homologous to the EBV BNRF1, BORF2, major capsid protein (BcLF1), DNA polymerase (BALF5), major DNA-binding protein (BALF2), BXLF1, BVRF1, BVRF2 and BXRF1 reading frames.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic analyses of MDV of chickens (Buckmaster et al, 1988) underline some of the difficulties in predicting the likely biological properties of herpesviruses on the basis of genetic data alone. Although arguments can be brought forward in an attempt to resolve the apparent inconsistencies between the biological and genetic data in the case of MDV (see Introduction to this paper and Honess et al, 1989a) it is clear that our understanding of the correlation between the genetic content of herpesviruses and their biological properties is far from complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marek's disease (MD), a lymphoma of thymus-derived lymphocytes in chickens, is caused by Marek's disease herpesvirus (MDV), which has been classified as an alphaherpesvirus (Buckmaster et al, 1988). MDV DNA consists of a unique long sequence (UL) and a unique short sequence (US) both flanked by a set of inverted repeats (terminal repeat long region, TRL ; inverted repeat long region, IRL ; inverted repeat short region, IRS ; and terminal repeat short region, TRS) ( Fig.…”
Section: Introductionmentioning
confidence: 99%